Bentuk dan Strategi Tindak Tutur Direktif dalam Dialog Film Melodylan Karya Asri Aci - Yulita, Fika Tri; Wahyono, Hari; Shalima, Irsyadi (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This research is motivated by the use of directive speech acts found in the dialogues of Asri Aci's MeloDylan film. The formulation of the problem of this research, namely (1) what are the forms of directive speech acts contained in the dialogue of the film MeloDylan by Asri Aci? and (2) what are the directive speech act strategies contained in the dialogues of Asri Aci's MeloDylan? The aims of the study were (1) to obtain a description of the directive speech acts in Asri Aci's MeloDylan dialogue, and (2) to obtain a description of the directive speech act strategies in Asri Aci's MeloDylan. The research subject is the form and strategy of directive speech acts in the dialogue of Asri Aci's Melodylan film. The data collection methods and techniques used are the observing method and the note taking technique. The results of the study found data in the form of directive speech acts. namely (1) data on the form of directive speech acts of commands, (2) data on the forms of directive speech acts on requests, (3) data on the forms of directive speech acts on invitations, (4) on the forms of speech acts on directives of advice, (5) on the forms of speech acts on directives of criticism, and (6) data on the forms of directive speech acts on prohibitions. As for directive speech act strategy data, namely (1) explicit directive speech act strategy data, (2) direct directive speech act strategy data, (3) indirect directive speech act strategy data, and (4) non-literal directive speech act strategy data.